Accounting Education and Sustainability Reporting among Prestigious European Universities - Liliana Ionescu-Feleagă; Sînziana-Maria Rîndașu; Monica Aureliana Petcu; Ioana Ignat; Oana-Cristina Stoica; Adrian Isip; Daniel-Marius Iordache (Amfiteatru Economic, 2025)
The accounting profession is fundamentally oriented towards meeting the dynamic needs of the business environment and society. Considering the European Union’s recent sustainability reporting requirements, this study examines the main sustainability topics covered in the accounting curricula of prestigious European higher education institutions (HEIs) to highlight the contribution of the academic environment in maintaining the accounting profession’s relevance in sustainability reporting. Based on the QS ranking, 40 HEIs offering programmes in accounting have been identified, of which 65% include sustainability items in their curriculum. Through a content analysis of 157 syllabi from the final sample of 26 universities, from 39 bachelor’s and 55 master’s programmes, the results of the study indicate the development of an extensive framework of sustainability elements included in accounting education, where mainly technical aspects are prevalent, to the detriment of social and ethical ones. The analysis identified six dimensions of sustainable development topics, with sustainability reporting as the primary dimension, facilitated by secondary dimensions intended to provide context in terms of needs, drivers, and control mechanisms. The study’s findings contribute to the existing literature on sustainability accounting education by exploring this phenomenon in prestigious European HEIs, which, in an uncertain context, assumed a pioneering role in maintaining the accounting profession’s relevance. The proposed framework provides a roadmap for other universities, encouraging the development of mimetic factors in updating the accounting education. Moreover, this study has important implications for the profession and the business environment